Avant-Garde toen 2 : De twintiger jaren. - Debruyn, M.; van Peer, W. (Turnhout : De Warande, 1984)
Tatlin, W. ; Lissitzky, El ; Majakowski, W. ; Arp, Hans ; Cernigoj, A. ; Klek, J. ; Petrov, M. ; Radovic, I. ; Siepancic, E. ; Clemens, R. ; Dexel, W. ; Grosz, G.
Avant-Garde toen 2 - De twintiger jaren, De Warande, Turnhout, 27/1 - 26/2/1984
Nederlands
kunstcatalogus
Keywords: Rusland; Joegoeslavië; Duitsland; Nederland; België